Sustainability accounting - Belal, Ataur Rahman; Cooper, Stuart; Giordano-Spring, Sophie; Maurice, Jonathan; Cho, Charles H. (Advances in environmental accounting & management, ISSN 1479-3598, 2018)
Advances in Environmental Accounting Managementaims to advance knowledge of the management of corporate environmental impacts. It aims to increase the awareness of management accounting practitioners, investors, and other stakeholders of the financial and social consequences of corporate environmental impacts.
Keywords: Sustainable development reporting; Social accounting; Business & Economics : Accounting : General; Accounting